The role of Demodex folliculorum in pathogenesis of rosacea - Małgorzata Wieteska; Dominik Maj; Adrianna Gorecka; Anna Gorajek; Monika Wacławska; Aleksandra Chałupnik (Kazimierz Wielki University, 2022)
Introduction and objective: Rosacea is a common chronic inflammatory disease that affects approximately 10% of the population globally. The exact pathogenesis of rosacea remains unknown. However, there are considered several factors such as genetic predisposition, environmental impact, immune dysregulation, as well as presence of microorganisms. The aim of the study is to review recent knowledge about the relationship between rosacea and Demodex folliculorum. The information used in the presented analysis was obtained by searching academic research databases: Google Scholar and PubMed. An abbreviated description of the state of knowledge: Demodex folliculorum is a microscopic mite that resides in the hair follicles and sebaceous glands of the skin. Current studies show that Demodex folliculorum plays an important role in pathogenesis of rosacea. That is related with the induction of excessive pro-inflammatory skin response combined with increase in inflammation mediators. Moreover in patients with rosacea there is observed a nearly 6-fold increase in Demodex folliculorum density in comparison to general population. Increased number of mites is associated with local immunosuppression that may predispose to the development of rosacea. The presence of Demodex mites is related not only with acute course and prolonged duration of the disease, but also with higher probability of recurrence. Summary: Demodex folliculorum is involved in the pathogenesis of rosacea. Moreover, as a parasite, it significantly decreases the quality of patient's life. Therefore, patients with severe rosacea should be examined for the presence of Demodex mites. In case of detection, regardless of its quantitative load, antiparasitic drug should be recommended.